Was Kiriath-jearim in Judah or in Benjamin? - Leṿin, Yigʾal 1963- (2021)
The town of Kiriath-jearim, identified at Deir el-ꜤAzar above the village of Abu Ghosh, has come to scholarly attention recently due to the renewed excavations led by I. Finkelstein and T. Römer. Based on their preliminary finds and on their reading of the biblical texts, they have interpreted the Iron Age IIB–C fortified compound that they have begun to expose on the summit of the site as a northern Israelite fortified compound, ‘aimed at dominating the vassal kingdom of Judah’. This paper reexamines the position of Kiriath-jearim on the border between Judah and Benjamin according to both the biblical texts and the site’s geographical location, within the context of the ongoing discussions on the biblical tribal territories, that of Benjamin in particular, the ‘ark narrative’ and other texts that mention Kiriath-jearim, and challenges the excavators’ interpretation of the character and purpose of the site during the Iron Age II.